Effectiveness and safety of Maxing Shigan Decoction for community-acquired pneumonia: a systematic review and meta-analysis of randomized controlled trials - Ling, Yutong; Liu, Xuehan; Zhang, Bingrui; Xiao, Qionghua; Shuai, Zhihao; Bai, Han; Cai, Rui; Li, Shuangsang; Yuan, Mingyi; Zhang, Yanxia (Frontiers in Medicine, 2025)
Background and ObjectiveCommunity-acquired pneumonia (CAP) is an acute lung infection disease with high morbidity and mortality. The treatment of CAP has become more and more challenging due to the gradual increase of antibiotic resistance and adverse events. Relevant evidence indicates that Maxing Shigan Decoction (MXSG) may play a unique therapeutic advantage. Our aim is to evaluate the overall effectiveness and safety of MXSG for CAP.MethodsEight databases (PubMed, Embase, the Cochrane Library, CNKI, Wanfang, VIP, Yiigle, and Sinomed) were searched from their inception to January 20, 2025. Randomized controlled trials evaluating the effectiveness and safety of MXSG alone or in combination with conventional western medicine (WM) for CAP were included. We conducted meta-analysis by RevMan 5.4 software or just performed qualitative analysis.ResultsWe included 81 RCTs with 6682 participants in total. Compared with western medicine (WM) alone, MXSG plus WM showed a more beneficial effect on reducing the duration of fever (MD = −1.58 days, 95% CI: −1.88 to −1.29, p < 0.00001), cough (MD = −2.30 days, 95% CI: −2.61 to −1.99, p < 0.00001), phlegm (MD = −2.40 days, 95% CI: −2.56 to −2.23, p < 0.00001), dyspnea (MD = −2.11 days, 95% CI: −2.73 to −1.49, p < 0.00001), pulmonary crepitation (MD = −2.13 days, 95% CI: −2.47 to −1.79, p < 0.00001) and length of hospitalization (MD = −1.38 days, 95% CI: −2.54 to −0.23, p = 0.02). Furthermore, MXSG plus WM was significantly superior to WM in promoting the absorption of lung inflammation (MD = −3.31 days, 95% CI: −4.17 to −2.46, p < 0.00001) and improving forced expiratory volume in the first second (MD = 0.54 L, 95% CI: 0.21 to 0.87, p = 0.001). The incidence of adverse events was 3.60% in MXSG plus WM group and 5.38% in WM group, but the difference was not significant (p = 0.06).ConclusionModerate or low certainty of evidence suggested that compared with WM alone, MXSG combined with WM may have potential effectiveness on relieving the clinical symptoms, promoting the absorption of lung inflammation, improving lung function, and reducing hospitalization length with a good safety for patients with CAP. In the future, high-quality double-blind RCTs should be required to confirm the effectiveness and safety on CAP.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023404693, identifier CRD42023404693.